Field Evaluation of Neem Seed Oil Against the Habul Whitefly Acaudaleyrodes rachipora (Singh) Aleyrodidae: Homoptera) on Acacia senegal Seedlings - Sundaraj, R; Murugesan, S; Mishra, R N (Annals of Arid Zone, 2016)
An experiment was conducted to study the bioefficacy of neem seed. oil alone and in combination with two conventional insecticides, viz., monocrotophos and endosulfan against the babul whitefly Acaudaleyrodes rachipora on Acacia senegal seedling. The results demonstrated that the neem seed oil at 05% alone is good enough to control this pest and its combination with either 0.1% monocrotophos or endosulfan did not show any superiority than neem seed oil alone to A. rachipora.